Analysis of Delta(9) fatty acid desaturase gene family and their role in oleic acid accumulation in Carya cathayensis kernel - Si, Xiaolin; Lyu, Shiheng; Hussain, Quaid; Ye, Hongyu; Huang, Chunying; Li, Yan; Huang, Jianqin; Chen, Jianjun; Wang, Ketao (Frontiers in Plant Science, 2023)
Carya cathayensis, commonly referred to as Chinese hickory, produces nuts that contain highquality edible oils, particularly oleic acid (18:1). It is known that stearoyl-ACP desaturase (SAD) is the first key step converting stearic acid (C18:0, SA) to oleic acid (C18:1, OA) in the aminolevulinic acid (ALA) biosynthetic pathway and play an important role in OA accumulation. Thus far, there is little information about SAD gene family in C. cathayensis and the role of individual members in OA accumulation. This study searched the Chinese Hickory Genome Database and identified five members of SAD genes, designated as CcSADs, at the whole genome level through the comparison with the homologous genes from Arabidopsis. RNA-Seq analysis showed that CcSSI2-1, CcSSI2-2, and CcSAD6 were highly expressed in kernels. The expression pattern of CcSADs was significantly correlated with fatty acid accumulation during the kernel development. In addition, five full-length cDNAs encoding SADs were isolated from the developing kernel of C. cathayensis. CcSADs-green fluorescent protein (GFP) fusion construct was infiltrated into tobacco epidermal cells, and results indicated their chloroplast localization. The catalytic function of these CcSADs was further analyzed by heterologous expression in Saccharomyces cerevisiae, Nicotiana benthamiana, and walnut.Functional analysis demonstrated that all CcSADs had fatty acid desaturase activity to catalyze oleic acid biosynthesis. Some members of CcSADs also have strong substrate specificity for 16:0-ACP to synthesize palmitoleic acid (C16:1, PA). Our study for the first time documented SAD gene family in C. cathayensis and the role of CcSSI2-1, CcSSI2-2, and CcSAD6 in OA accumulation, which could be important for future improvement of OA content in this species via genetic manipulation.